2012
DOI: 10.1001/archinternmed.2012.4268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Screening Abdominal Aortic Aneurysms Very Efficiently (SAAAVE) Act on Abdominal Ultrasonography Use Among Medicare Beneficiaries

Abstract: The impact of the SAAAVE Act on AAA screening was modest and was based on abdominal ultrasonography use that it did not directly reimburse. The SAAAVE Act had no discernable effect on AAA rupture or all-cause morality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…Despite the introduction of the SAAAVE Act in 2007, screening for AAA remains underutilized [19]. Additionally, more recent data suggest that the implementation of the SAAAVE Act has not had any discernible effect on AAA rupture rate or AAA-related mortality, presumably due to its severe underutilization [20]. …”
Section: Clinical Studies On Aaamentioning
confidence: 99%
“…Despite the introduction of the SAAAVE Act in 2007, screening for AAA remains underutilized [19]. Additionally, more recent data suggest that the implementation of the SAAAVE Act has not had any discernible effect on AAA rupture rate or AAA-related mortality, presumably due to its severe underutilization [20]. …”
Section: Clinical Studies On Aaamentioning
confidence: 99%
“…However, this is a fairly narrow screening program, and it has been shown that the SAAAVE Act has had no discernable effect on AAA rupture or all-cause mortality [7]. …”
Section: Introductionmentioning
confidence: 99%
“…AAA screening using a hand-held ultrasound device was faster for early detection: our study required only 4 minutes per patient. Moreover, it would be cheaper than traditional AAA screening programs that have a modest effect on AAA rupture or all-cause mortality [55,56] with an estimated cost per patient of $53 [57]. Some recent opinions suggest ultra sound should be brought to the point of patient care, and should be in the black bag of every general practitioner [58,59], or should form part of the periodic physical examination [60].…”
Section: Discussionmentioning
confidence: 99%